Analysis of E-Banking Acceptance in Oman: The Case of Islamic Banks’ Customers - Echchabi, Abdelghani; Al-Hajri, Salim; Tanas, Islam Nazier (International Journal of Islamic Economics and Finance (IJIEF), 2019)
The main objective of this study is to examine the factors that influence the customers’ intention to adopt E-banking services in Oman across the Islamic Banking sector. This research endeavours to assess the willingness of the Islamic banks’ customers to adopt these services rather than the traditional banking methods. Accordingly, a sample of 300 Islamic banks' customers were surveyed in different districts of Oman. Afterwards, linear regression and one sample t-test were utilized in order to analyse the gathered data. The findings showed that customers have high tendency of embracing and utilizing E-banking services as opposed to the conventional services. Additionally, the results revealed that relative advantage, self-efficacy, ease of use, and facilitating conditions are the fundamental factors that impact the selection of E-banking by Islamic banks' customers in Oman. However, uncertainty had no significant effect on the intention of Islamic banks’ customers to use E-banking services. These findings would significantly contribute to the theory, and the way that Islamic banking sector would be practiced and regulated.